2022
DOI: 10.33448/rsd-v11i2.25464
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética em espécies e híbridos interespecíficos de Physalis baseada em caracteres morfoagronômicos

Abstract: Physalis L. é um dos gêneros mais importantes da família Solanaceae, contendo 120 espécies botanicamente identificadas. As espécies de Physalis possuem uma grande variedade genética, devido ao elevado número de espécies botanicamente identificadas, que garante características peculiares de interesse econômico. Apesar do conhecimento dessas características, pouco se tem feito para o melhoramento genético dessa pequena fruta. Para se iniciar o melhoramento é necessário realizar a análise da diversidade genética … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Under these circumstances, the low level of diversity still available in cultivated populations may be of limited agronomic importance. However, there are reports of native germplasm from other species of Physalis, or from interspecific hybrids within the genus, being used for hybridization inasmuch as they represent a source of alleles conferring resistance to viral diseases (CELy et al, 2015;SILVA-JÚNIoR et al, 2022). In addition, some studies have shown that variability within-populations is greater than between-populations; therefore, it is important to design tools that allow the evaluation of individual plants in order better to exploit intrapopulation resources (CHACÓN et al, 2016).…”
Section: Introduction Of Germplasmmentioning
confidence: 99%
“…Under these circumstances, the low level of diversity still available in cultivated populations may be of limited agronomic importance. However, there are reports of native germplasm from other species of Physalis, or from interspecific hybrids within the genus, being used for hybridization inasmuch as they represent a source of alleles conferring resistance to viral diseases (CELy et al, 2015;SILVA-JÚNIoR et al, 2022). In addition, some studies have shown that variability within-populations is greater than between-populations; therefore, it is important to design tools that allow the evaluation of individual plants in order better to exploit intrapopulation resources (CHACÓN et al, 2016).…”
Section: Introduction Of Germplasmmentioning
confidence: 99%
“…There are also many native species of the genus physalis in the country. The introgression of the genes of these species has made it possible to expand the genetic base(Silva Júnior et al, 2022).…”
mentioning
confidence: 99%